Class Struggle from Above: The Canadian State, Industrial Legality, and (the Never-Ending Usage of) Back-to-Work Legislation - Smith, Charles (Labour / Le Travail, 2020)
Analyzes the historical context of class struggle and strikes under capitalism, the restrictions on strike activity in Canada, and the entrenchment of back-to-work legislation under the Canadian neoliberal regime.